The psychology-pedagogical preconditions of conductor's work in the condition of extra-curricular activities (Pedagogy of Higher and Secondary Education, 2007)
In this article the psychology- pedagogical preconditions of conductor's work, principles, forms and methods of organization of conductor's extra- curricular activities are considered.
Keywords: psychology-pedagogical preconditions; conductor's activity; extra-curricular work; relations; attention; aim; performance cf musical work; evolving education